THE IMPACT OF INTERNAL ORGANIZATIONAL ENVIRONMENT FACTORS ON THE EFFICIENCY OF HEALTH - Mamdouh Nada Khalaf Alenezi, Naif Khalaf Alshammari, Sultan Saqer Almutairi, Nawaf Bandar Almutairi (Chelonian Research Foundation, 2022)
Quality in healthcare services is paramount, necessitating a shift from focusing solely on quantity to emphasizing outcomes and values. This cross-sectional study delves into the internal organizational and environmental factors crucial for enhancing the efficiency of health services provision. It explores healthcare professionals' perspectives on these internal factors and strategies for optimizing patient outcomes. In this context, a survey was conducted among healthcare professionals , garnering responses from 66 participants. Findings indicate a consensus among 21 respondents on the necessity for continuous education to elevate the standard of care. Communication skills were highlighted by 38 participants as key to improving medical performance, with 34 expressing interest in attending expert lectures for skill enhancement. Additionally, 25 respondents emphasized the significance of increased salaries in improving healthcare service standards. While 63 respondents underscored the equal importance of healthcare services and equipment, 3 disagreed. Enhancing internal organizational factors and healthcare service quality emerges as a critical pathway to enhancing overall performance. Strategies such as ongoing education through expert lectures, improving communication and leadership skills, adopting advanced equipment, and offering competitive salaries are pivotal in driving efficiency and effectiveness in healthcare services. Keywords: Internal organizational-environment factors, efficiency of health services, healthcare professionals' perspectives.